Radicals and Radical Ions in Chemistry, Life and Material Sciences - Georg Gescheidt (CHIMIA)
Radicals are almost everywhere. This compilation shows how and where these short-lived species are generated and which methods are utilized fortheir investigation in our laboratory. Three examples from the fields of supramolecular chemistry, pharmacologically active compounds, and material science are outlined.